Smoke detection using remote sensing technique - Asmala, A.; Ayof, M. N.; Agus, S.B.; Sakidin, H.; Sharifah Sakinah, S.A. (Universiti Teknikal Malaysia Melaka, 2006)
Particulate matter sizing less than 10 micrometers widely known as PM10 is one of the major constituents of the thick smoke haze phenomenon, which occured in Malaysia during September 1997. In this study, seven scenes of NOAA-14 AVHRR satellite data were acquired in order to determine and map PM10 over Malaysia. Five locations of air pollution station were chosen where PM10 was measured. Initially, preprocessing tasks namely: atmospheric and geometric correction were implemented befor further image processing job. Next, band 1 of AVHRR data with wavelength ranging from 0.58 to 0.68 micrometers were calibrated to compensate for post-launch sensor deradation. Cloud separation was then carried out using visual and thresholding technique. Relationship between the satellite and the corresponding PM10 AQI (air quality index) at the selected stations was established using linear regression model. The model was then used to map the concentration of PM10 over Malaysia. The result indicates that remote sensing technique usin band 1 of NOAA-14 AVHRR data was capable to determine PM10 concentration quantitatviely and spatially in continous manner. Finally, accuracy was assessed using Root-mean-square error technique.